Analysis Of Land Use In The Southern Part Of Bali Using Fusion Techniques - I Kadek Adiana Putra; Takahiro Osawa; Made Sudiana Mahendra (Graduate Study of Environmental Sciences, Postgraduate Program of Udayana University, 2018)
The southern part of Bali is a central region of tourism, especially in the Sub District of North Kuta, Kuta and South Kuta. The rapid development of tourism is with increasing infrastructure development. Monitor and analyze need to the land use. In this study a fusion technique with HSV method as the combination with ALOS AVNIR-2 2008 and ALOS PRISM in 2008, to estimate of the level of accuracy of image fusion with ALOS AVNIR-2 and subsequent for the analysis of land use in southern part of Bali. Results of the accuracy test with Google Earth showed land use result fusion has high accuracy with overall accuracy of 83. 5%. Analyze of land use showed that significant decrease of moor area in Jimbaran hill, due to rapid development of infrastructure of tourism is very rapid and then extensive residential areas have increased particularly in Sub district of the North Kuta.